(untitled) (Research, Society and Development, 2021)
Objective: To understand the practice of semiology in nursing professional practice. Methodology: This is an integrative literature review study. The inclusion criteria were articles published between 2017 and 2021, in Portuguese, English and Spanish, available in full and that answered the guiding question "What has been produced by professionals regarding the use of semiology by nursing professionals? The descriptors "Nursing", "Physical Examination" and "Nursing Process" were used. Results: Fourteen articles were obtained, most of them (65%) with a quantitative basis, five of the selected articles had a sample larger than fifty interviewees. Regarding the year of publication, one article was obtained from the year 2021, four from 2020, four from 2019, three from 2018, and two from 2017. With this, three sub-items were prepared for discussion, being them: "Professional training in relation to the use of semiology practices", "Use of semiology in daily activities" and "Use of technology in professional training". Thus, it is possible to understand that the nursing professional provides care at all levels of health care, from basic care to complex care and rehabilitation, at all these levels, attributes expected of the professional are necessary, such as assessment, monitoring, critical thinking, decision making, among others. Conclusion: In short, the practice of semiology allows holistic and individualized care, allowing performing daily activities assertively and accurately.